2021
DOI: 10.1007/s00466-021-02112-3
|View full text |Cite
|
Sign up to set email alerts
|

A Bayesian multiscale CNN framework to predict local stress fields in structures with microscale features

Abstract: Multiscale computational modelling is challenging due to the high computational cost of direct numerical simulation by finite elements. To address this issue, concurrent multiscale methods use the solution of cheaper macroscale surrogates as boundary conditions to microscale sliding windows. The microscale problems remain a numerically challenging operation both in terms of implementation and cost. In this work we propose to replace the local microscale solution by an Encoder-Decoder Convolutional Neural Netwo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(16 citation statements)
references
References 46 publications
2
14
0
Order By: Relevance
“…Indeed, we found that the U-Net made erroneous stress predictions near the image boundary when trained on smaller images, or on large images without padding. Similar errors appear in related work such as [30], where the receptive field of 104 × 104 𝑝𝑥 was larger than the image size of 32 × 32 𝑝𝑥 and images were not appropriately padded; indeed, nonphysical stress predictions were visible near the image boundary in figures included in [31]. Other related work has shown that inappropriate image padding can worsen predictions of mechanical response [42].…”
Section: Cnn Design and Trainingsupporting
confidence: 70%
See 1 more Smart Citation
“…Indeed, we found that the U-Net made erroneous stress predictions near the image boundary when trained on smaller images, or on large images without padding. Similar errors appear in related work such as [30], where the receptive field of 104 × 104 𝑝𝑥 was larger than the image size of 32 × 32 𝑝𝑥 and images were not appropriately padded; indeed, nonphysical stress predictions were visible near the image boundary in figures included in [31]. Other related work has shown that inappropriate image padding can worsen predictions of mechanical response [42].…”
Section: Cnn Design and Trainingsupporting
confidence: 70%
“…Their StressNet model applied a series of convolutional filters to images of the beam geometry, and predicted the Von Mises stress for each pixel of the image; these values were compared to the stress on the same model computed by FE. This architecture has recently been extended to predict the mechanical response of fiber-reinforced composites at the microscale [29] and mesoscale [30], and also to predict stress concentrations around microscale pores in a multiscale FE model [31]. Alternative CNN architectures such as generative adversarial network [32] or image colorization networks [33] used to predict stress from microstructural images with varying levels of success.…”
Section: Introductionmentioning
confidence: 99%
“…The multiscale framework that we use here is a direct extension of our previous work [Krokos et al, 2021]. As mentioned in section [2.2], the examples that we show in this work are dedicated to linear elasticity for porous media made of a homogeneous matrix with a random distribution of microscale features that are modelled as spherical voids.…”
Section: Global-local Frameworkmentioning
confidence: 99%
“…Our paper addresses these two points by extending our previous work [Krokos et al, 2021], while adding two novel algorithmic elements. First, we manage to tackle 3D problems by using geometric learning where instead of voxelised images we learn directly from the mesh that is used to perform the FE simulations.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation